2014
DOI: 10.1063/1.4895596
|View full text |Cite|
|
Sign up to set email alerts
|

Probe diagnostics of electron distributions in plasma with spatial and angular resolution

Abstract: Articles you may be interested inAssessment of plasma impedance probe for measuring electron density and collision frequency in a plasma with spatial and temporal gradients Phys. Plasmas 21, 053501 (2014); 10.1063/1.4874321Experimental measurements of spatial plasma potentials and electron energy distributions in inductively coupled plasma under weakly collisional and nonlocal electron kinetic regimes This paper discusses the spatial resolution that is required to study inhomogeneous, low-temperature plasmas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In turn, for the Langmuir probe used here, the EEDF is proportional to the second derivative of the probe current with respect to the probe potential V (see, for example, [24])…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, for the Langmuir probe used here, the EEDF is proportional to the second derivative of the probe current with respect to the probe potential V (see, for example, [24])…”
Section: Resultsmentioning
confidence: 99%
“…The probe measurement technique is used to measure the spectra of Penning electrons. Much work has been reported over the last three decays and extensive reviews are available [24][25][26][27]. The combination of digital to analog converters and analog converters provides very fast data collection, and several commercial systems are available, including compensated probes for high frequency discharges.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows the probe characteristics and their derivatives of the measuring electrode in pure helium. The probe CVCs have a classical form with electron and ion saturation currents and a transition region between them [21].…”
Section: Resultsmentioning
confidence: 99%
“…The probe measurement technique is used to measure the spectra of Penning electrons [21][22][23]. The combination of digital to analog and analog converters provides fast data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Probe diagnostic methods have made rapid progress in recent decades, and, in addition to single probes, double probes and emissive probes have also been proven to be useful in various situations [2,22,25,[33][34][35][36]. A significant development in probe diagnostics was made by Druyvesteyn, who demonstrated that the second derivative of the single probe current provided the electron energy distribution function (EEDF) of the plasma [36,37].…”
Section: Introductionmentioning
confidence: 99%